Identifikasi Pusat Pertumbuhan dan Analisis Interaksi Spasial Perekonomian di Provinsi Jawa Timur - Irhas Fudhail; Herman Sambodo; Sodik Dwi Purnomo (Universitas Batanghari, 2021)
East Java Province is one of the largest regions and has the second highest GDP on Java Island. However, based on the Williamson index the level of income distribution within regions districts/cities is still low. This study intent to analyze areas that become growth pole and spatial economic interactions in East Java Province in 2009 and 2018. The analyses used in this research are gravity model analysis and scalogram analysis. The results of scalogram analysis and centrality showed that in 2009 there were 3 districts/cities included in Hierarchy I, 5 districts/cities in Hierarchy II, 6 districts/cities in Hierarchy III, 9 districts/cities in Hierarchy IV, 12 districts/cities in Hierarchy V and 3 districts/cities VI. While in 2018 there were 8 districts/cities in Hierarchy I, 10 districts/cities in Hierarchy II, 11 districts/cities in Hierarchy III, 4 districts/cities in Hierarchy IV, 3 districts/cities in Hierarchy V and 2 districts/cities in Hierarchy VI. Growth pole areas within hinterland areas in 2009 to 2018 increased. From 2009 to 2018 hinterland areas that interact strongly with the city of Surabaya such as Sidoarjo Regency, Gresik Regency and Bangkalan Regency. The results imply the necessity to increase interaction or cooperation both in the economic and social between the regions which are the center of growth and the hinterland region such as in the economic sector.